Perception and Attitude towards French for specific purposes among Linguistics Students in the University of Calabar - Egbe-John, Agatha Umo; Umukoro, Gloria Mayen (ELT Worldwide: Journal of English Language Teaching, 2024)
The need for specialized language instruction arises from the growing demand for professionals proficient in French within specific contexts. The objective of this study was to explore the effectiveness of FSP in improving language skills and cultural knowledge among learners in the Department of Linguistics, University of Calabar. To achieve the purpose of this study, three research questions were posed. A literature review was carried out according to the study variables. Descriptive research design was adopted for the study. The target population consists of all students and instructors in the Department of Linguistics at the University of Calabar who are enrolled in or teaching French language courses. The study sample consisted of 33 respondents which involved 26 learners and 7 instructors were purposively sampled from the Department of Linguistics, University of Calabar. Questionnaire was the instrument used for qualitative data collection. Qualitative data analysis was conducted using thematic analysis techniques which involved simple percentages. The results indicate a gap in language needs and challenges for learners in the Department of Linguistics. Secondly, FSP instruction impacts learners’ language proficiency and cultural understanding. Finally, the results indicate that FSP instruction's impact on the perceptions and attitudes of learners and instructors towards FSP is high. The findings from this study have several implications for the design and implementation of FSP instruction to enhance language proficiency, promote cultural understanding, and foster cross-cultural communication skills among learners. Educators and curriculum developers can leverage these findings to design effective FSP-based language programs that cater to the diverse needs of language learners.